2021
DOI: 10.3390/ijerph182312387
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Stage SEM—Artificial Neural Network Analysis of the Rewards Effects on Self Perceived Performance in Healthcare

Abstract: Healthcare managers consider the rewards and performances of employees as central elements of their activities due to the challenges caused by the phenomenon of healthcare employees’ emigrating to higher-income countries, which has reduced patient satisfaction and led to a negative image of hospitals. In this context, this paper analyzes how employee rewards influence the employees’ self-perceived performances in the hospital units of the emergency medical system in Romania. Using structural equation modeling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Because common method biases can have potentially serious effects on research findings, it is important to avoid this risk. The research relies on the designed questionnaire and forms self-administered data (data on independent and dependent variables emanate from the same respondent and the same measurement), therefore common method bias (CMB) may exist and affect the validity of survey results and the reliability of data [ 60 ]. According to the causes and solutions of CMB proposed by Podsakoff, P.M., this paper mainly tries to avoid common method bias from the following three perspectives [ 61 , 62 ]: Procedural Remedy …”
Section: Methodsmentioning
confidence: 99%
“…Because common method biases can have potentially serious effects on research findings, it is important to avoid this risk. The research relies on the designed questionnaire and forms self-administered data (data on independent and dependent variables emanate from the same respondent and the same measurement), therefore common method bias (CMB) may exist and affect the validity of survey results and the reliability of data [ 60 ]. According to the causes and solutions of CMB proposed by Podsakoff, P.M., this paper mainly tries to avoid common method bias from the following three perspectives [ 61 , 62 ]: Procedural Remedy …”
Section: Methodsmentioning
confidence: 99%
“…The study by Bocean et al (2021) about two-stage SEM-artificial neural network analysis of the effects of the reward on self-perceived performance in healthcare-used structural equation modelling to examine the impact of recognition on employee performance. The findings revealed that both financial motivation and recognition of employees' merits significantly influence employees' self-perceived performances.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Over the past few years, as large cities continue to introduce various inclusive integration policies, more and more migrant families are migrating to cities. The increase in household size enhances the migrants' sense of belonging in the city [81], while also increasing spending on house rent, food, and entertainment.…”
Section: Structural Equation Modeling (Sem) Theoretical Basismentioning
confidence: 99%